Toward a penology of organizational offending - Sutton, James E (Punishment & society, 2023)
The punishment of organizational offending has largely been overlooked by penologists, despite the fact that organizational actors such as corporations and the state perpetrate the most serious forms of offending. Accordingly, this paper represents a step toward foregrounding organizational offending within the discipline of penology. We begin by discussing the implications of several Classical School ideals and theories of punishment for organizational offending, with special emphases on challenges and contradictions. We then review control strategies that are unique to organizational offending, and we go on to contemplate how expressive and non-institutional tactics might potentially factor into how organizational offending is punished. When taken together, these sections reveal the limitations of penology's traditional assumptions of an individual offender and individual offending. We conclude by outlining our view of what a penology of organizational offending should accomplish.